Barrier laminate and packaging bag
By using a single-layer barrier film on paper-based materials, combining hydroxide polypeptide ester, expandable layered silicate and electric-carrying resin, the problem of difficult to balance the performance and environmental sustainability of water vapor and gas barriers in the prior art is solved, and the dual goals of efficient barriers and environmental sustainability are achieved.
Patent Information
- Application Number
- JP2024050834
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-16
- Filing Date
- 2024-03-27
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-03-13
AI Technical Summary
The prior art is difficult to meet the requirements of efficient barriers and environmental sustainability while providing water vapor and gas barrier properties to paper-based materials, especially in reducing plastic use and environmental burdens.
A single-layer barrier film is used, including hydroxypolyurethane, swellable layered silicate and cationic resin, to improve water vapor and gas barrier performance, while reducing the amount of coating and improving the recyclability of paper-based materials.
The performance of high water vapor and gas barriers has been improved, which reduces the amount of coating on the barrier layer, reduces the environmental burden, and improves the recovery rate of pulp, promoting environmental protection and sustainability.
Smart Images

Figure 0007666685000001 
Figure 0007666685000002 
Figure 0007666685000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a barrier laminate and a packaging bag using the same. [Background technology]
[0002] Packaging materials having a paper base material imparted with gas barrier properties such as oxygen barrier properties and water vapor barrier properties have conventionally been used in packaging foods, medical products, electronic components, etc., for the purpose of preventing deterioration of the contents.
[0003] A common method for imparting water vapor barrier properties or gas barrier properties to a paper substrate is to laminate a synthetic resin film having excellent gas barrier properties onto the paper substrate. However, materials in which a synthetic resin film or the like is laminated onto a paper substrate have problems in terms of the environment, since it is difficult to recycle the paper and synthetic resin after use.
[0004] Therefore, there has been progress in the development of gas barrier materials that use paper as a base material without using synthetic resin films, etc. For example, Patent Document 1 describes a technology in which a paper barrier material has a gas barrier layer and a heat seal layer provided in this order on a paper base material, and the hydroxyl and acid groups of the resin used in the gas barrier layer are controlled. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2021-138434 A Summary of the Invention
[0006] The paper barrier material described in Patent Document 1 has a single barrier layer and is capable of reducing the amount of plastic material used. However, this is not sufficient from the viewpoint of water vapor barrier properties. The present disclosure provides a barrier laminate that achieves high compatibility between water vapor barrier property and gas barrier property with a small number of layers (for example, even if the barrier layer is a single layer), and further allows the coating amount of the barrier layer to be reduced, thereby reducing the burden on the environment.
[0007] <1> A barrier laminate having a barrier layer on at least one surface of a paper substrate, the barrier layer is a single layer, The water vapor permeability of the barrier layer at 40°C and 90% RH is 50g / m 2 Less than day, The oxygen permeability of the barrier layer at 23°C and 50% RH is 10.0 mL / m 2 ·day·atm or less, The water vapor permeability of the barrier laminate measured at 40°C and 90% RH in accordance with JIS-Z-0208:1976 is 50 g / m 2 Less than day, When a CPP film was laminated to the barrier laminate, the oxygen permeability at 23°C and 50% RH was 10.0 mL / m 2 ·day·atm or less, A barrier laminate, wherein the recovery rate of pulp after re-defibration of the barrier laminate is 85 mass % or more. <2> the barrier layer comprises a hydroxy polyurethane and a swellable layered silicate; <1> 2. The barrier laminate according to claim 1 . <3> The barrier layer further contains a cationic resin. <2> 2. The barrier laminate according to claim 1 .
[0008] <4> A barrier laminate having a barrier layer on at least one surface of a paper substrate, The barrier layer comprises a hydroxy polyurethane, a swellable layered silicate, and a cationic resin. <5> The content of the cationic resin in the barrier layer is 1.0 to 20.0% by mass. <3> or <4> 2. The barrier laminate according to claim 1 . <6> The content of the hydroxy polyurethane in the barrier layer is 30.0 to 80.0% by mass. <2> ~ <5> 13. The barrier laminate according to claim 12, <7> The content of the swellable layered silicate in the barrier layer is 5.0 to 30.0% by mass. <2> ~ <6> 13. The barrier laminate according to claim 12,
[0009] <8> The barrier layer further comprises at least one selected from the group consisting of a water-dispersible polymer other than hydroxypolyurethane and a water-soluble polymer other than hydroxypolyurethane; the water-dispersible polymer comprises at least one selected from the group consisting of a styrene-butadiene copolymer, an acrylic resin, an olefin-unsaturated carboxylic acid copolymer, and a polyolefin resin; The water-soluble polymer includes at least one selected from the group consisting of a vinyl alcohol polymer, a (meth)acrylic acid polymer, a polyethylene glycol, a water-soluble polyamide, a polyacrylamide, a polyamine, a polycarboxylic acid, and a water-soluble cellulose derivative. <1> ~ <7> 13. The barrier laminate according to claim 12, <9> the total content of the water-suspendable polymer other than the hydroxy polyurethane and the water-soluble polymer other than the hydroxy polyurethane in the barrier layer is 2.0 to 50.0% by mass; <8> 2. The barrier laminate according to claim 1 .
[0010] <10> the barrier laminate further has a heat seal layer on the side where the barrier layer is laminated, the heat seal layers of the barrier laminate are heat sealed together under conditions of 150°C, 0.2 MPa, and 1 second, and the heat seal strength when the obtained sample is peeled off using a tensile tester is 2.0 N / 15 mm or more; <1> ~ <9> 13. The barrier laminate according to claim 12, <11> The total coating weight of the barrier layer and the heat seal layer is 12 g / m 2 Below is the <10> 2. The barrier laminate according to claim 1 . <12> When a CPP film is laminated to the barrier laminate, the oxygen permeability at 23°C and 85% RH is 10.0 mL / m 2 ·day·atm or less, <1> ~ <11> 13. The barrier laminate according to claim 12, <13> <1> ~ <12> A packaging bag comprising the barrier laminate according to any one of claims 1 to 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In this specification, the range "X to Y" means "X or more and Y or less." When a numerical range is described in stages, the upper and lower limits of each numerical range can be combined arbitrarily. In addition, in this specification, unless otherwise specified, operations and measurements of physical properties are performed under the conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.
[0012] At least one embodiment of the present disclosure (hereinafter also referred to as a first embodiment) is a barrier laminate having a barrier layer on at least one surface of a paper substrate, the barrier layer is a single layer, The water vapor permeability of the barrier layer at 40°C and 90% RH is 50g / m 2 Less than day, The oxygen permeability of the barrier layer at 23°C and 50% RH is 10.0 mL / m 2 ·day·atm or less, The water vapor permeability of the barrier laminate measured at 40°C and 90% RH in accordance with JIS-Z-0208:1976 is 50 g / m 2 Less than day, When a CPP film is laminated to the barrier laminate, the oxygen permeability at 23°C and 50% RH is 10 mL / m 2 ·day·atm or less, The recovery rate of pulp after re-defibration of the barrier laminate is 85% by mass or more.
[0013] At least one embodiment of the present disclosure (hereinafter also referred to as a second embodiment) is a barrier laminate having a barrier layer on at least one surface of a paper substrate, The barrier layer relates to a barrier laminate containing (A) a hydroxy polyurethane, (B) a swellable layered silicate, and (C) a cationic resin. In the second embodiment, the barrier layer containing the above components (A) to (C) alone exhibits excellent water vapor barrier properties and gas barrier properties, but the laminate may further have a barrier layer other than the barrier layer. The present inventors have conducted extensive research into a barrier laminate that achieves both high water vapor barrier property and high gas barrier property with a small number of layers (for example, even if the barrier layer is a single layer) and further allows the coating amount of the barrier layer to be reduced, and have found that the above-mentioned problems can be solved by providing the above-mentioned barrier laminate.
[0014] In the first embodiment, first, the water vapor permeability of the barrier laminate measured under conditions of 40°C and 90% RH in accordance with JIS-Z-0208:1976 is 50 g / m 2 ·day. The water vapor permeability is less than 40 g / m 2 ·day or less, and 30g / m 2 ・day or less is more preferable, and 20g / m 2 15 g / m 2 It is even more preferable that the g / m 2 It is especially preferable that the maximum permeability is 8 g / m 2 The above range indicates that the water vapor barrier property is very high. The lower limit is not particularly limited because the lower the better, but it is preferably 0 g / m 2 ·day or more, 1g / m 2 ·day or more, 2g / m 2 ·day or more, 3g / m 2 The water vapor permeability can be controlled, for example, by selecting the thickness of the barrier layer or the components contained in the barrier layer.
[0015] In addition, when a CPP film was laminated onto the barrier laminate, the oxygen permeability at 23°C and 50% RH was 10.0 mL / m 2·day·atm or less. The oxygen permeability is 8.0mL / m 2 ·day·atm or less, and 5.0mL / m 2 ·day·atm or less is more preferable, and 3.0mL / m 2 1.0 mL / m 2 1.5 mL / m 2 ·day·atm or less is more preferable, and 1.0mL / m 2 It is especially preferable that the concentration is less than 0.5 L / m 2 The above range indicates that the oxygen barrier property is very high. The lower limit is not particularly limited because the lower the better, but it is preferably 0.0 mL / m 2 ·day·atm or more, 0.1mL / m 2 The oxygen permeability can be controlled, for example, by selecting the thickness of the barrier layer or the components contained in the barrier layer.
[0016] The barrier laminate has a barrier layer on at least one surface of a paper substrate. In a first embodiment, the barrier layer is a single layer. The water vapor transmission rate of the barrier layer at 40° C. and 90% RH is 50 g / m 2 Less than ·day. The water vapor permeability of the barrier layer is 40 g / m 2 ·day or less, and 30g / m 2 ・day or less is more preferable, and 20g / m 2 15 g / m 2 It is even more preferable that the g / m 2 It is especially preferable that the maximum permeability is 8 g / m 2 It is particularly preferable that the temperature is 0.1 -day or less. The lower limit is not particularly limited because the lower the better, but it is preferably 0 g / m 2 ·day or more, 1g / m 2 ·day or more, 2g / m 2·day or more, 3g / m 2 ·day or more. The water vapor permeability of the barrier layer is measured by the measurement method described in the Examples below.
[0017] In addition, the oxygen permeability of the barrier layer at 23°C and 50% RH is 10.0 mL / m 2 ·day·atm or less. The oxygen permeability of the barrier layer is 8.0 mL / m 2 ·day·atm or less, and 5.0mL / m 2 ·day·atm or less is more preferable, and 3.0mL / m 2 1.0 mL / m 2 1.0 mL / m 2 It is especially preferable that the concentration is 0.7 mL / m or less. 2 ·day·atm or less is even more preferable, and 0.5L / m 2 It is particularly preferable that the temperature is 100°C or less. The lower limit is not particularly limited because the lower the better, but it is preferably 0.0 mL / m 2 ·day·atm or more, 0.1mL / m 2 ·day·atm or higher. The oxygen permeability of the barrier layer is measured by the measurement method described in the Examples below.
[0018] Regarding the first aspect of the present disclosure, the fact that the barrier layer satisfies the above water vapor permeability and oxygen permeability indicates that the barrier layer has very high water vapor barrier property and gas barrier property in a single layer. Since the barrier layer can achieve such high water vapor barrier property and gas barrier property in a single layer, the coating amount of the barrier layer can be reduced, enabling the product to be made lighter. On the other hand, in the second aspect of the present disclosure, the barrier layer of the barrier laminate contains a hydroxy polyurethane, a swellable layered silicate, and a cationic resin, so that the labyrinth effect of the swellable layered silicate can be efficiently exerted, and as a result, very high gas barrier property and water vapor barrier property can be exhibited, which contributes to solving the above-mentioned problems. In addition, the recovery rate of pulp after re-disintegration of the barrier laminate can be increased, biodegradability can be improved, and a barrier laminate capable of reducing the burden on the environment can be obtained. Furthermore, since the number of layers of the barrier laminate can be reduced, the occurrence of blisters can be suppressed and production can be performed with a reduced number of steps. In the first embodiment, whether the barrier layer is a single layer can be confirmed by preparing a cross section along a direction perpendicular to the paper plane and observing the cross section with an electron microscope, or by non-destructive observation using an X-ray CT. For example, the water vapor permeability and oxygen permeability can be set within the above ranges by selecting the material used for the barrier layer.
[0019] The recovery rate of the pulp after the barrier laminate is re-defibrated is 85% by mass or more. A recovery rate in the above range indicates that the barrier laminate has a high pulp content and is highly recyclable. In addition to satisfying the above-mentioned water vapor permeability and oxygen permeability, it also indicates that a small coating amount can achieve both high water vapor barrier property and gas barrier property. The recovery rate of the pulp is preferably 88% by mass or more, more preferably 90% by mass or more, and even more preferably 92% by mass or more. There is no upper limit, but it is preferably 99% by mass or less, 98% by mass or less, or 97% by mass or less. The pulp recovery rate can be controlled by the coating amount of the barrier layer, the content of the layered inorganic compound (swellable layered silicate) in the barrier layer, the basis weight of the paper base material, and the like.
[0020] In addition, when a CPP film was laminated onto the barrier laminate, the oxygen permeability at 23°C and 85% RH was 10.0 mL / m 2·day·atm or less, and 8.0mL / m 2 ·day·atm or less is more preferable, and 5.0mL / m 2 1.0 mL / m 2 1.0 mL / m 2 It is especially preferable that the concentration is 1.5 mL / m 2 ·day·atm or less is more preferable, and 1.0mL / m 2 It is particularly preferable that the temperature is 100°C or less. The lower limit is not particularly limited because the lower the better, but it is preferably 0.0 mL / m 2 ·day· ATM or higher, 0.1mL / m 2 ·day·atm or higher.
[0021] The oxygen permeability at 85% RH falling within the above range indicates that the film exhibits sufficient gas barrier properties even in a high humidity environment. The oxygen permeability at 5% RH can be adjusted to fall within the above range by selecting the material used for the barrier layer. The materials of the barrier laminate will be described below.
[0022] <Paper base material> The barrier laminate includes a paper substrate. The paper substrate is not particularly limited, and any known paper material can be used. The pulp constituting the paper base material is preferably mainly composed of plant-derived pulp, and is mainly composed of wood pulp. Examples of wood pulp include hardwood pulp and softwood pulp. Examples of non-wood pulp include cotton pulp, hemp pulp, kenaf pulp, bamboo pulp, etc. Materials other than pulp fibers, such as synthetic fibers such as rayon fibers and nylon fibers, may also be blended as secondary paper materials as long as they do not impair the effects of the present invention.
[0023] Specific examples of the paper substrate include bleached kraft paper, unbleached kraft paper, fine paper, paperboard, liner paper, coated paper, one-sided gloss bleached kraft paper, glassine paper, graphene paper, etc. Among these, bleached kraft paper, unbleached kraft paper, fine paper, and one-sided gloss bleached kraft paper are preferred. Bleached kraft paper and one-sided gloss bleached paper are more preferred, and one-sided gloss bleached kraft paper is even more preferred.
[0024] Additives may be added to the paper base material. Examples of additives include pH adjusters (sodium bicarbonate, sodium hydroxide, etc.), dry strength agents (polyacrylamide, starch, etc.), wet strength agents (polyamide polyamine epichlorohydrin resin, melamine-formaldehyde resin, or urea-formaldehyde resin), internal sizing agents (rosin-based, alkyl ketene dimer, etc.), drainage retention improvers, antifoaming agents, fillers (calcium carbonate, talc, etc.), dyes, etc. These additives may be used alone or in combination of two or more. The content of the additives is not particularly limited and may be within the range that is usually used.
[0025] (Basic weight) The basis weight of the paper substrate is not particularly limited, but for example, for packaging bag applications, it is 20 g / m 2 More than 150g / m 2 Less than 30 g / m is preferable. 2 More than 100g / m 2 Less than 40 g / m is more preferable. 2 More than 70g / m 2 The following is even more preferred: The basis weight of the paper base material is measured in accordance with JIS P 8124:2011.
[0026] (paper thickness) The thickness of the paper base material is not particularly limited, but for example, for packaging bag applications, it is preferably 20 μm to 150 μm, more preferably 25 μm to 100 μm, and even more preferably 30 μm to 50 μm. The thickness of the paper base material is measured in accordance with JIS P 8118:2014.
[0027] (Oken type smoothness) The smoothness of the paper substrate is not particularly limited. For example, the Oken smoothness of the surface on which the barrier layer is to be provided is preferably 5 seconds or more, more preferably 10 seconds or more. The upper limit is not particularly limited, but for example, it is preferably 2000 seconds or less, more preferably 1000 seconds or less. The Oken smoothness of the paper substrate is measured in accordance with JIS P 8155:2010.
[0028] (Manufacturing method of paper base material) The method for producing the paper base material includes a method of making a paper stock containing pulp. The paper stock may further contain additives. Examples of the additives include the additives listed above.
[0029] The stock can be prepared by adding additives to a pulp slurry. The pulp slurry is obtained by beating pulp in the presence of water. The pulp beating method and beating device are not particularly limited, and may be the same as known beating methods and beating devices. The pulp content in the stock is not particularly limited, and may be within a range that is usually used. For example, it is 60% by mass or more and less than 100% by mass with respect to the total mass of the stock.
[0030] Papermaking from the stock can be carried out by standard methods. For example, the stock can be cast onto a wire or the like, dehydrated to obtain a wet paper, and multiple wet papers can be stacked as necessary, and this single-layer or multi-layer wet paper can be pressed and dried. In this case, if multiple wet papers are not stacked, a single-layer paper is obtained, and if multiple wet papers are stacked, a multi-layer paper is obtained. When multiple wet papers are stacked, an adhesive can be applied to the surface of the wet paper (the surface on which other wet papers are stacked).
[0031] <Barrier layer> In the first embodiment, the barrier laminate has a single barrier layer on at least one surface of a paper substrate. As described above, the barrier layer exhibits high water vapor barrier properties and gas barrier properties. There are no particular limitations on the material used for the barrier layer as long as it can exhibit the water vapor barrier properties and gas barrier properties. For example, the following known resins can be used.
[0032] Resins that can be used for the barrier layer include polyolefin resins (polyethylene, polypropylene, etc.), vinyl chloride resins, styrene resins, styrene / butadiene copolymers, acrylonitrile / styrene copolymers, acrylonitrile / butadiene copolymers, ABS resins, AAS resins, AES resins, vinylidene chloride resins, polyurethane resins, poly-4-methylpentene-1 resins, polybutene-1 resins, vinylidene fluoride resins, vinyl fluoride resins, fluororesins, polycarbonate resins, polyamide resins, acetal resins, polyphenylene oxide resins, and polyesters. Examples of the resin include resins (polyethylene terephthalate, polybutylene terephthalate, etc.), polyphenylene sulfide resins, polyimide resins, polysulfone resins, polyethersulfone resins, aromatic polyester resins, polyarylate resins, olefin / unsaturated carboxylic acid copolymers, styrene / unsaturated carboxylic acid copolymers, acrylic resins, polyvinyl alcohol and modified resins thereof, polyacrylic acid and salts thereof, polysaccharide resins such as cellulose derivatives, starch and derivatives thereof, naturally occurring thermosetting resins such as natural rubber and shellac, and modified products thereof.
[0033] (Hydroxy Polyurethane) In the first and second aspects, in order to exhibit high water vapor barrier properties and gas barrier properties, the barrier layer preferably contains a hydroxy polyurethane. Hydroxy polyurethane refers to a polyurethane having a hydroxyl group. The hydroxyl value of the hydroxy polyurethane is preferably 100 to 500 mgKOH / g, more preferably 150 to 400 mgKOH / g, and further preferably 200 to 350 mgKOH / g. The above hydroxyl value increases the cohesive force of the hydroxy polyurethane, making it easier to exhibit high barrier properties.
[0034] The hydroxy polyurethane may have an acid group. The acid value of the hydroxy polyurethane is preferably 50 to 100 mgKOH / g, more preferably 10 to 70 mgKOH / g, and further preferably 15 to 60 mgKOH / g. The acid value and hydroxyl value of the hydroxy polyurethane can be measured by a titration method in accordance with JIS K 1557:2007.
[0035] The hydroxy polyurethane may be a commercially available product, such as HPU W-001, HPU W-003, or HPU-W013A (all manufactured by Dainichiseika Color & Chemicals Co., Ltd.). The content of hydroxy polyurethane in the barrier layer is preferably 30.0 to 80.0 mass%, more preferably 40.0 to 75.0 mass%, even more preferably 50.0 to 70.0 mass%, even more preferably 55.0 to 68.0 mass%, and even more preferably 60.0 to 66.0 mass%. By being in the above range, the water vapor barrier property and the gas barrier property are more easily improved. In addition, by being in the above range, the strength of the barrier layer is good, and when a heat seal layer is provided on the barrier layer, the heat seal property is good.
[0036] (Water-suspended polymer, water-soluble polymer) In the first and second aspects, it is preferable that the barrier layer further contains at least one selected from the group consisting of water-suspendable polymers other than hydroxypolyurethanes and water-soluble polymers other than hydroxypolyurethanes. The water-suspendable polymers and water-soluble polymers may be selected from those mentioned above as resins that may be used in the barrier layer.
[0037] The water-dispersible polymer other than the hydroxy polyurethane preferably includes at least one selected from the group consisting of a styrene-butadiene copolymer, an acrylic resin, an olefin-unsaturated carboxylic acid copolymer, and a polyolefin resin. The water-soluble polymer other than hydroxy polyurethane preferably includes at least one selected from the group consisting of vinyl alcohol-based polymers, (meth)acrylic acid-based polymers, polyethylene glycol, water-soluble polyamides, polyacrylamides, polyamines, polycarboxylic acids, and water-soluble cellulose derivatives, and more preferably includes at least one selected from the group consisting of vinyl alcohol-based polymers and (meth)acrylic acid-based polymers.
[0038] By using such a water-dispersible polymer or water-soluble polymer, the film-forming properties of the barrier layer can be improved, and the water vapor barrier properties and gas barrier properties can be improved. When forming a barrier layer by aqueous coating, a water-soluble polymer is more effective at improving film formability than a water-suspendable polymer. Furthermore, from the viewpoint of improving the water resistance of the barrier layer and improving the water vapor barrier properties, it is preferable to use a water-suspendable polymer in addition to a water-soluble polymer. In other words, it is preferable that the barrier layer contains a water-suspendable polymer and a water-soluble polymer. In this case, the water-suspendable polymer is preferably an olefin-unsaturated carboxylic acid copolymer, and more preferably an ethylene-(meth)acrylic acid copolymer. Furthermore, the water-soluble polymer is preferably a vinyl alcohol polymer. The mass ratio of the water-suspendable polymer to the water-soluble polymer in the barrier layer (water-suspendable polymer:water-soluble polymer) is preferably 20:1 to 1:2, more preferably 10:1 to 2:3, even more preferably 5:1 to 3:4, and even more preferably 4:1 to 4:5.
[0039] (Water-suspended polymer) Styrene / butadiene copolymer Styrene-butadiene copolymers are copolymers obtained by emulsion polymerization of monomers consisting of styrene compounds such as styrene, α-methylstyrene, vinyltoluene, pt-butylstyrene, and chlorostyrene, butadiene compounds such as 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene, as well as other compounds copolymerizable with these. As the styrene-based compound, styrene is preferred, and as the butadiene-based compound, 1,3-butadiene is preferred.
[0040] Styrene-butadiene copolymers can also be used that are commercially available, such as LX407S12 (manufactured by Zeon Corporation) as an acid-modified styrene-butadiene copolymer binder.
[0041] Styrene / acrylic copolymer The styrene / acrylic copolymer is a copolymer obtained by emulsion polymerization of a monomer consisting of a styrene compound such as styrene, α-methylstyrene, vinyltoluene, pt-butylstyrene, or chlorostyrene, an acrylic compound such as acrylic acid, methacrylic acid, (meth)acrylic acid ester, (meth)acrylamidopropanesulfonic acid, or (meth)acrylic acid sulfoalkyl sodium salt (the number of carbon atoms in the alkyl group is 2 to 3), or other compounds copolymerizable therewith. As the styrene compound, styrene is preferred, and as the acrylic compound, acrylic acid, methacrylic acid, acrylic acid ester, or methacrylic acid ester is preferred, with acrylic acid and acrylic acid ester being more preferred. As the (meth)acrylic acid ester, an acrylic acid alkyl ester is preferred, and the number of carbon atoms in the alkyl group is preferably 1 to 6.
[0042] As the styrene / acrylic copolymer, commercially available products can also be used. For example, an example of a styrene-acrylic copolymer binder is JONCRYL HSL-9012 (manufactured by BASF).
[0043] <Olefin / unsaturated carboxylic acid copolymer> The olefin / unsaturated carboxylic acid copolymer is a copolymer obtained by emulsion polymerization of a monomer consisting of an olefin, particularly an α-olefin such as propylene or ethylene, and an unsaturated carboxylic acid such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, butene tricarboxylic acid, or the like, an unsaturated polycarboxylic acid alkyl ester having at least one carboxy group, such as itaconic acid monoethyl ester, fumaric acid monobutyl ester, and maleic acid monobutyl ester, or other compound copolymerizable therewith.
[0044] The olefin is preferably ethylene or an α-olefin, more preferably ethylene, and the unsaturated carboxylic acid monomer is preferably acrylic acid, methacrylic acid, itaconic acid, fumaric acid, or the like.
[0045] As a specific example of an olefin / unsaturated carboxylic acid copolymer, for example, an aqueous dispersion of ethylene-acrylic acid copolymer ammonium salt is commercially available as ZAIXXEN (registered trademark) AC (copolymerization ratio of acrylic acid: 20%, manufactured by Sumitomo Seika Chemicals), and can be easily obtained and used.
[0046] <Polyolefin resin> The polyolefin resin is preferably a polymer of ethylene or α-olefin, more preferably polyethylene. Commercially available polyolefins can also be used. For example, HYDRECT HS (manufactured by DIC Corporation) can be used as a polyolefin resin binder.
[0047] (Water-soluble polymer) <Vinyl alcohol polymer> An example of the vinyl alcohol polymer is polyvinyl alcohol. The polyvinyl alcohol preferably has a saponification degree of 85.0 to 99.5 mol %, more preferably 90.0 to 99.0 mol %. As the polyvinyl alcohol, commercially available products may be used. For example, the EXCEVAL series (manufactured by Kuraray Co., Ltd.) can be mentioned.
[0048] <(Meth)acrylic acid polymer> Examples of (meth)acrylic acid-based polymers include polyacrylic acid, polymethacrylic acid, and salts thereof. Examples of salts include sodium poly(meth)acrylate and ammonium poly(meth)acrylate. Commercially available (meth)acrylic acid-based polymers can also be used. For example, an aqueous solution of ammonium polyacrylate can be Aron A-30 (manufactured by Toa Gosei Co., Ltd.).
[0049] Other examples of the water-soluble polymer that can be used include known polyethylene glycol, water-soluble polyamide, polyacrylamide, polyamine, polycarboxylic acid, and water-soluble cellulose derivatives. Examples of the polycarboxylic acid include polymaleic acid, acrylic acid-maleic acid copolymer, and polyglucuronic acid. Examples of the water-soluble cellulose derivatives include methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, methylhydroxypropyl cellulose, and methylhydroxyethyl cellulose.
[0050] The weight average molecular weight of the water-suspendable polymer and the water-soluble polymer is preferably 10,000 or more, more preferably 20,000 or more, and preferably 10 million or less, more preferably 5 million or less. The weight average molecular weight of the water-suspendable polymer is measured using gel permeation chromatography (standard: polystyrene). The weight average molecular weight of the water-soluble polymer is measured using gel permeation chromatography (standard: polyethylene glycol).
[0051] The total content of the water-suspendable polymer other than hydroxy polyurethane and the water-soluble polymer other than hydroxy polyurethane in the barrier layer is preferably 2.0 to 50.0 mass%, more preferably 5.0 to 45.0 mass%, even more preferably 10.0 to 35.0 mass%, and even more preferably 15.0 to 25.0 mass%. By being in the above range, it becomes easier to improve the water vapor barrier property and the gas barrier property, and the heat sealability becomes better.
[0052] (Layered inorganic compounds) In the first embodiment, in order to facilitate improving the water vapor barrier property and the gas barrier property, the barrier layer may contain a layered inorganic compound. The layered inorganic compound has a tabular shape. By using a layered inorganic compound in the barrier layer, the flat layered inorganic compound is easily laminated almost parallel to the plane (surface) of the paper substrate. In this way, the area where the layered inorganic compound is not present in the plane direction is small, so that the permeation of water vapor is easily suppressed. In addition, since the flat layered inorganic compound is arranged parallel to the plane of the paper substrate in the thickness direction, the water vapor in the layer permeates while bypassing the layered inorganic compound, and the permeation of water vapor is suppressed by the maze effect. As a result, the barrier layer is easily able to exhibit excellent water vapor barrier properties.
[0053] The average thickness of the layered inorganic compound is preferably 200 nm or less. The average thickness of the layered inorganic compound is preferably 120 nm or less, more preferably 50 nm or less, even more preferably 25 nm or less, and particularly preferably 10 nm or less. The smaller the thickness of the layered inorganic compound, the greater the number of laminations of the layered inorganic compound in the barrier layer, and therefore the greater the water vapor barrier properties can be exhibited. The lower limit of the thickness of the layered inorganic compound is not particularly limited, but is preferably 2 nm or more. Here, the average thickness of the layered inorganic compound contained in the barrier layer is obtained as follows. A magnified photograph of the cross section of the barrier layer is taken using an electron microscope. At this time, the magnification is set so that about 20 to 30 pieces of the layered inorganic compound are included in the screen. The thickness of each layered inorganic compound is measured, and the average value of the thicknesses thus measured is calculated to be the average thickness of the layered inorganic compound.
[0054] The average length of the layered inorganic compound is preferably 1 μm or more and 100 μm or less. When the average length is 1 μm or more, the layered inorganic compound is easily arranged parallel to the paper base material. Also, when the average length is 100 μm or less, there is little concern that a part of the layered inorganic compound will protrude from the barrier layer. The average length of the layered inorganic compound is more preferably 50 μm or less, even more preferably 30 μm or less, and particularly preferably 15 μm or less. Here, the average length of the layered inorganic compound contained in the barrier layer is obtained as follows. A magnified photograph of the cross section of the barrier layer is taken using an electron microscope. At this time, the magnification is set so that about 20 to 30 layered inorganic compounds are contained within the screen. The length of each layered inorganic compound within the screen is measured. Then, the average value of the obtained lengths is calculated to be the average length of the layered inorganic compound. The length of the layered inorganic compound may also be expressed as a particle diameter.
[0055] The aspect ratio of the layered inorganic compound is preferably 50 or more. When the aspect ratio is 50 or more, the water vapor barrier property is more easily improved. The aspect ratio of the layered inorganic compound is preferably 80 or more, more preferably 300 or more, and particularly preferably 500 or more. The larger the aspect ratio, the more the water vapor permeation is suppressed and the water vapor barrier property is improved. In addition, the larger the aspect ratio, the less the amount of the layered inorganic compound added can be. The upper limit of the aspect ratio is not particularly limited, and from the viewpoint of the viscosity of the coating liquid, it is preferably about 10,000 or less, more preferably about 5,000 or less, and even more preferably about 2,000 or less. Here, the aspect ratio is, as described above, a value obtained by taking an enlarged photograph of the cross section of the barrier layer using an electron microscope, and dividing the average length of the layered inorganic compound obtained by the average thickness.
[0056] Specific examples of layered inorganic compounds include micas such as mica group and brittle mica group, bentonite, kaolinite (kaolin mineral), pyrophyllite, talc, smectite, vermiculite, chlorite, septe chlorite, serpentine, stilpnomelane, and montmorillonite.
[0057] Among these, in particular, from the viewpoint of improving the barrier property, it is preferable to contain one or more of mica and bentonite, and mica or bentonite is more preferable. Specific examples of mica include synthetic mica (e.g., swelling mica, non-swelling mica), white mica (muscovite), sericite (sericite), gold mica (phlocopite), black mica (biotite), fluorine gold mica (artificial mica), red mica, soda mica, vanadium mica, illite, chin mica, paragonite, brittle mica, etc. Specific examples of bentonite include montmorillonite.
[0058] In the first and second embodiments, the barrier layer preferably contains a swellable layered silicate such as swellable mica as the layered inorganic compound. The barrier layer preferably contains hydroxy polyurethane and a swellable layered silicate. The swellable layered silicate is a layered inorganic compound that swells in water and the layers are easily cleaved by shear to a thickness on the order of nanometers. By combining hydroxy polyurethane and a swellable layered silicate, the swellable layered silicate is dispersed thinly and with a high aspect ratio in the hydroxy polyurethane resin film that originally has high gas barrier performance, and the labyrinth effect provides even higher gas barrier performance. Examples of the swellable layered silicate include sodium tetrasilicic mica, sodium hectorite, lithium taeniolite, fluorine phlogopite, sodium smectite, and sodium montmorillonite. The swellable layered silicate is preferably a swellable mica such as sodium tetrasilicic mica. Examples of the swellable mica among commercially available swellable layered silicates include NTO-05 (manufactured by Topy Industries) and Somasif ME300B-4T (manufactured by Katakura Co-op Agri Co., Ltd.).
[0059] The content of the swellable layered silicate in the barrier layer is preferably 5.0 to 30.0 mass%, more preferably 10.0 to 25.0 mass%, and even more preferably 13.0 to 24.0 mass%. By being in the above range, the water vapor barrier property and gas barrier property can be more easily improved.
[0060] (cationic resin) In the first and second aspects, the barrier layer preferably further contains a cationic resin in addition to the hydroxy polyurethane and the swellable layered silicate. By containing the cationic resin, the gas barrier property and water vapor barrier property, particularly the water vapor barrier property, are greatly improved, and it becomes easier to achieve the oxygen permeability and water vapor permeability in the above-mentioned specific ranges. The swellable layered silicate is likely to have an anionic particle surface and a cationic particle end surface, so that the surface and end surface attract each other to form a card-house aggregation structure. By adding a cationic resin, the anionic groups on the particle surface can be blocked with cations, and the card-house aggregation structure can be destroyed. Therefore, the steric aggregation of the swellable layered silicate can be suppressed, and the swellable layered silicate can be aligned parallel to the plane of the paper base material, and the labyrinth effect can be fully expressed. As a result, very high gas barrier properties and water vapor barrier properties can be exhibited.
[0061] Specific examples of cationic resins include polyalkylene polyamines, polyamide compounds, modified polyamide compounds, polyamidoamine-epihalohydrin or formaldehyde condensation reaction products, polyamine-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamidoamine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea compounds, polyamine polyurea compounds, polyamidoamine polyurea compounds and polyamidoamine compounds, polyethyleneimine, polyvinylpyridine, amino-modified acrylamide compounds, polyvinylamine, and polydiallyldimethylammonium chloride. Among them, the cationic resin is preferably a modified polyamide compound, more preferably a modified polyamide resin. The modified polyamide resin may be a commercially available product, such as SPI203(50)H manufactured by Taoka Chemical Co., Ltd.
[0062] The content of the cationic resin in the barrier layer may be appropriately selected depending on the type of material used in the barrier layer, such as hydroxy polyurethane and swellable layered silicate, etc. From the viewpoint of further improving the barrier property and / or heat sealability, the content of the cationic resin in the barrier layer is preferably 1.0 to 20.0 mass%, more preferably 1.0 to 10.0 mass%, even more preferably 1.5 to 8.0 mass%, even more preferably 1.8 to 5.0 mass%, and particularly preferably 2.0 to 3.0 mass%.
[0063] The surface charge of the cationic resin is preferably 0.1 to 10 meq / g, more preferably 0.1 to 5.0 meq / g, even more preferably 0.1 to 4.0 meq / g, even more preferably 0.1 to 2.0 meq / g, and particularly preferably 0.2 to 1.0 meq / g. When the surface charge of the cationic resin is equal to or higher than the lower limit, the effect of adding the cationic resin can be more fully obtained, whereas when the surface charge is equal to or lower than the upper limit, the effect of the cationic resin can be more fully exhibited while suppressing aggregation of the swellable layered silicate. The surface charge of the cationic resin is measured by the method described below. First, a sample polymer is dissolved in water to obtain a solution with a polymer concentration of 1 ppm. 0.001N sodium polyethylene sulfonate is dropped into the solution using a charge analyzer Mutek PCD-04 (manufactured by BTG) to measure the amount of charge.
[0064] The barrier layer may contain, as necessary, a dispersant, a surfactant, a defoamer, a wetting agent, a dye, a color adjuster, a thickener, and the like, to the extent that the specific barrier properties described above are not impaired.
[0065] (Coating amount of barrier layer) The coating amount of the barrier layer is not particularly limited, but from the viewpoint of barrier properties, it is preferably 1 g / m2 as a solid content after drying. 2 More preferably, 2 g / m 2From the viewpoint of redisintegration, it is preferably 15 g / m 2 More preferably, it is 10 g / m or less. 2 Less than 8 g / m, more preferably 2 and even more preferably 6 g / m 2 The following is the result. The thickness of the barrier layer is preferably from 1 to 20 μm, and more preferably from 2 to 10 μm.
[0066] (Method of forming a barrier layer) The method for forming the barrier layer is not particularly limited. For example, a coating liquid for the barrier layer is prepared by dispersing at least one resin selected from the group consisting of water-dispersible polymers and water-soluble polymers other than hydroxy polyurethane, hydroxy polyurethane, swellable layered silicate, and cationic resin in a solvent. The obtained coating liquid for the barrier layer is preferably applied to a paper substrate and dried to form a barrier layer.
[0067] The solvent for the barrier layer coating liquid is not particularly limited, and may be water or an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, or toluene. Among these, from the viewpoint of not causing problems with volatile organic solvents, the dispersion medium for the barrier layer coating liquid is preferably an aqueous medium, and more preferably water. In this specification, an aqueous medium is a medium containing 50% by mass or more of water.
[0068] The device used for applying the barrier layer coating solution is not particularly limited, and may be appropriately selected from commonly used coating devices, such as an air knife coater, a blade coater, a gravure coater, a rod blade coater, a roll coater, a reverse roll coater, a Mayer bar coater, a curtain coater, a die slot coater, a champlex coater, a metering blade type size press coater, a short dwell coater, a spray coater, a gate roll coater, and a lip coater.
[0069] <Heat seal layer> In the first and second embodiments, the barrier laminate may further have a heat seal layer on the side where the barrier layer is laminated. In the first embodiment, even if the heat seal layer has barrier properties, it is classified as a heat seal layer if it is provided for the purpose of imparting heat sealability. In the first embodiment, the heat seal layer does not meet both the ranges of water vapor permeability and oxygen permeability of the barrier layer described above, for example. Alternatively, in the first embodiment, the heat seal layer may meet either the range of water vapor permeability or oxygen permeability of the barrier layer described above, for example. On the other hand, in the second embodiment, the heat seal layer may have a barrier property such as a water vapor barrier property or a gas barrier property. In the second embodiment, the heat seal layer may satisfy at least one or both of the ranges of the water vapor permeability and the oxygen permeability of the barrier layer described above. stomach.
[0070] The heat seal layer is a layer that is melted and bonded by heating, ultrasonic waves, etc. The heat seal layer preferably contains a water-dispersible resin. Examples of the water-dispersible resin include those mentioned above as water-suspendable polymers other than hydroxy polyurethane, and preferably, acrylic resins such as polyolefin resins, styrene / acrylic copolymers, and ethylene-(meth)acrylic acid copolymers. Examples of the resin include grease, ethylene-vinyl acetate copolymer, polyester resin, rubber-based resin, urethane resin, polyamide resin, etc. In addition to these resins, lubricants such as paraffin wax, carnauba wax, polyolefin-based wax, and pigments such as silica and kaolin may be added for the purpose of preventing blocking and improving oil resistance.
[0071] The heat seal layer is preferably a layer containing at least one resin selected from the group consisting of styrene / acrylic copolymers and polyolefin resins. Commercially available materials include styrene-acrylic aqueous dispersion (product name: XP8829, manufactured by Seiko PMC Co., Ltd.) and polyolefin aqueous dispersion (product name: Rhobarr320, manufactured by Dow Co., Ltd.). When the heat seal layer has a barrier property, the water vapor permeability of the heat seal layer at 40° C. and 90% RH is, for example, 1 to 100 g / m when converted into a thickness of 20 μm. 2 The oxygen permeability of the heat seal layer at 23°C and 50% RH is, for example, 1 to 100 mL / m2 when converted into a thickness of 20 μm. 2 ·day·atm.
[0072] (Coating amount of heat seal layer) The coating amount of the heat seal layer is not particularly limited, but from the viewpoint of heat sealability, it is preferably 1 g / m2 as a solid content after drying. 2 More preferably, 2 g / m 2 From the viewpoint of redisintegration, it is preferably 15 g / m 2 More preferably, it is 10 g / m or less. 2 Less than 8 g / m, more preferably 2 and even more preferably 6 g / m 2 The following is the result. The thickness of the heat seal layer is preferably 0.5 to 20 μm, and more preferably 1 to 10 μm.
[0073] (Method of forming heat seal layer) The method for forming the heat seal layer is not particularly limited. For example, a heat seal layer coating liquid is prepared by dispersing a water-dispersible resin in a solvent. The obtained heat seal layer coating liquid is preferably applied onto the barrier layer of the paper substrate and dried to form the heat seal layer.
[0074] The solvent for the heat seal layer coating liquid is not particularly limited, and may be water or an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, toluene, etc. Among these, from the viewpoint of not causing problems with volatile organic solvents, an aqueous medium is preferred as the dispersion medium for the heat seal layer coating liquid, and water is more preferred.
[0075] The total coating weight of the barrier layer and the heat seal layer is preferably 12 g / m 2More preferably, it is 11 g / m or less. 2 The above ranges mean that even a thin layer can exhibit very high gas barrier properties and water vapor barrier properties. In addition, the above ranges make it easier to increase the pulp recovery rate, making the product lighter, and improving biodegradability. The lower limit of the coating amount is not particularly limited, but is preferably 2 g / m 2 More preferably, it is 5 g / m 2 More preferably, it is 8 g / m 2 That's all.
[0076] The heat seal strength of a sample obtained by heat sealing the heat seal layers of a barrier laminate under conditions of 150°C, 0.2 MPa, and 1 second was measured when the sample was peeled off using a tensile tester. Preferably, the heat seal strength is 2.0 N / 15 mm or more, more preferably 2.5 N / 15 mm or more, even more preferably 2.8 N / 15 mm or more, and even more preferably 3.0 N / 15 mm or more. When the heat seal strength is in the above range, it is possible to prevent the bag from breaking during transportation of the contents. The upper limit is not particularly limited, but is preferably 10.0 N / 15 mm or less, 7.0 N / 15 mm or less, 5.0 N / 15 mm or less, or 4.0 N / 15 mm or less. In the first and second embodiments, the barrier laminate may have other layers in addition to the above-mentioned barrier layer and heat seal layer. In the second embodiment, the other layers may have barrier properties such as a water vapor barrier layer or a gas barrier layer.
[0077] <Production of Barrier Laminate> The method for producing the barrier laminate is not particularly limited and may be a known method. The method for producing the barrier laminate includes a step of first coating a barrier layer coating liquid on a paper substrate to form a barrier layer. If necessary, the method may include a step of coating a heat seal layer coating liquid on the surface of the paper substrate on which the barrier layer has been coated to form a heat seal layer. The formation of each layer is as described above. Each layer may be formed by successively coating and drying the coating liquid, or may be formed by simultaneous multi-layer coating followed by drying.
[0078] The drying equipment for drying each coating layer is not particularly limited, and known equipment can be used, such as a hot air dryer, an infrared dryer, a gas burner, and a hot plate.
[0079] In a first aspect of the present disclosure, the barrier laminate has a barrier layer on at least one surface of a paper substrate. The barrier laminate preferably has a paper substrate, a barrier layer, and a heat seal layer in this order. The barrier laminate may be a laminate consisting of only a paper substrate and a single-layer barrier layer, or may be a laminate consisting of only a paper substrate, a single-layer barrier layer, and a heat seal layer.
[0080] A second aspect of the present disclosure provides a barrier laminate having a barrier layer on at least one surface of a paper substrate, the barrier layer containing (A) a hydroxy polyurethane, (B) a swellable layered silicate, and (C) a cationic resin. According to this embodiment, extremely high water vapor barrier properties and gas barrier properties can be exhibited by the hydroxy polyurethane, the swellable layered silicate, and the cationic resin, and the coating amount of the barrier laminate can be reduced.
[0081] In the second embodiment, the barrier layer containing the above components (A) to (C) exhibits excellent water vapor barrier properties and gas barrier properties even when it is a single layer, but it may have two or more layers. In addition, in the second embodiment, when another layer (for example, a heat seal layer) is further included, the other layer may have barrier properties such as a water vapor barrier layer or a gas barrier layer. That is, in the second embodiment, the water vapor permeability and oxygen permeability may include the contribution of the other layer in addition to the barrier layer containing the above components (A) to (C).
[0082] The barrier laminate can be suitably used as a packaging material for food, cosmetics, daily necessities, medical products, electronic components, etc. The barrier laminate has very high water vapor barrier properties and gas barrier properties, so it can be suitably used as a packaging material for contents that have fragrances or odors. It can also be suitably used as a packaging material for food, cosmetics, daily necessities, medical products, electronic components, etc. that are exposed to high humidity conditions. The barrier laminate can be suitably used for soft packaging materials such as wrapping paper, packaging bags, lids, and labels; liquid containers such as milk cartons; packaging containers such as cups, trays, plates, lids, and laminated tubes; and the like. The contents to be packaged may be liquids, solids (granular materials, powders, etc.), or gels.
[0083] [Packaging bag] A packaging bag according to another embodiment of the present disclosure is a packaging bag made using the barrier laminate described above. Examples of the packaging bag include a standing pouch type, a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type (pillow seal type), a pleated seal type, a flat bottom seal type, a square bottom seal type, and a gusset type. The packaging bag of the present embodiment may be prepared by folding a barrier laminate having a heat seal layer or by overlapping two sheets of the barrier laminate so that the heat seal layers face each other, and heat sealing the peripheral edges of the laminate to form the above-mentioned shape. Alternatively, the packaging bag may be prepared by folding a barrier laminate or by overlapping two sheets of the barrier laminate, and bonding the peripheral edges of the laminate with an adhesive to form the above-mentioned shape.
[0084] [Oxygen permeability at 23℃ and 50% RH] The oxygen permeability of the barrier laminate was measured using an oxygen permeability measuring device (OX-TRAN2 / 22, manufactured by MOCON) under conditions of a temperature of 23°C and a relative humidity of 50%. Specifically, an isocyanate adhesive (a mixture of 10 parts of DIC Dry LX-500 and 1 part of DIC Dry KW-75, manufactured by DIC Corporation) was applied at a rate of 5 g / m2 to the barrier layer surface of the barrier laminate. 2 After coating, a CPP film (non-oriented polypropylene film: GP-32, manufactured by Hokuetsu Chemicals Co., Ltd.) having a thickness of 20 μm was laminated to form a laminated sheet. The oxygen permeability of the laminated sheet was measured at a temperature of 23°C and a relative humidity of 50% in accordance with JIS K7126-2:2006. The lower the oxygen permeability value, the better the oxygen barrier property. Note that the CPP film is laminated to make the measurement easier without being affected by the unevenness of the laminate, and the CPP film does not affect the oxygen permeability.
[0085] [Oxygen permeability at 23℃ and 85%RH] The oxygen permeability at 23°C and 85% RH was measured in the same manner as in the measurement of the oxygen permeability at 23°C and 50% RH, except that the conditions were changed to a temperature of 23°C and a relative humidity of 85%.
[0086] [Water vapor permeability] The water vapor permeability of the barrier laminates obtained in the examples and comparative examples was measured in accordance with JIS-Z-0208:1976 (cup method) Method B (40°C±0.5°C, relative humidity 90%±2%), with the side on which the barrier layer was provided facing inward.
[0087] [Oxygen permeability of the barrier layer at 23℃ and 50% RH] The oxygen permeability of the barrier layer of the barrier laminate at 23° C. and 50% RH can be calculated by the following procedure. (If materials for layers other than the barrier layer, such as the heat seal layer, are available) For example, when the barrier laminate has a layer structure of a paper substrate / barrier layer / heat seal layer, the calculation is performed as follows. The layer structure of the barrier laminate can be analyzed by cross-sectional observation using an electron microscope or X-ray CT measurement. Step 1: Measuring the oxygen permeability of the barrier laminate The oxygen permeability of the barrier laminate can be measured by the method described above. Step 2: Analyze the thickness of the heat seal layer. The thickness of the heat seal layer can be measured by cross-sectional observation using an electron microscope or X-ray CT measurement. A heat seal layer is applied to a non-oriented polypropylene film or a PET film so that the heat seal layer has the measured thickness, and the oxygen permeability of the heat seal layer alone can be inferred. Step 3: Calculate the oxygen permeability of the barrier layer alone based on the following formula from the oxygen permeability of the barrier laminate in step 1 and the oxygen permeability of the heat seal layer alone in step 2. At this time, the oxygen permeability of the paper base material does not need to be taken into consideration if glassine paper is not used as the paper base material (as a guideline, if the total light transmittance of the barrier laminate is less than 60%). 1 / P=1 / P1+1 / P2+···+1 / P n P: Oxygen permeability of the barrier laminate, P1, P2, ... P n : Oxygen permeability of each layer
[0088] (When materials for layers other than the barrier layer, such as the heat seal layer, are not available) For example, when the barrier laminate has a layer structure of a paper substrate / barrier layer / heat seal layer, the calculation is performed as follows. The layer structure of the barrier laminate can be analyzed by cross-sectional observation using an electron microscope or X-ray CT measurement. Step 1: Measuring the oxygen permeability of the barrier laminate The oxygen permeability of the barrier laminate can be measured by the method described above. Step 2: Analyze the material and thickness of the heat seal layer. The material of the heat seal layer can be analyzed by pyrolysis GC / MS, FT-IR analysis, Raman spectrum analysis, etc. The thickness of the heat seal layer can be measured by cross-sectional observation using an electron microscope or X-ray CT measurement, etc. The oxygen permeability of the heat seal layer alone can be inferred from the material and thickness of the heat seal layer. Step 3: Calculate the oxygen permeability of the barrier layer alone based on the following formula from the oxygen permeability of the barrier laminate in step 1 and the oxygen permeability of the heat seal layer alone in step 2. At this time, the oxygen permeability of the paper base material does not need to be taken into consideration if glassine paper is not used as the paper base material (as a guideline, if the total light transmittance of the barrier laminate is less than 60%). 1 / P=1 / P1+1 / P2+···+1 / P n P: Oxygen permeability of the barrier laminate, P1, P2, ... P n : Oxygen permeability of each layer
[0089] [Water vapor permeability of barrier layer] The water vapor permeability of the barrier layer of the barrier laminate at 40° C. and 90% RH can be calculated by the following procedure. (If materials for layers other than the barrier layer, such as the heat seal layer, are available) For example, when the barrier laminate has a layer structure of paper substrate / barrier layer / heat seal layer, the calculation is as follows: The layer structure of the barrier laminate can be analyzed by cross-sectional observation using an electron microscope, X-ray CT measurement, or the like (analysis method). Step 1: Measuring the water vapor permeability of the barrier laminate The water vapor permeability of the barrier laminate can be measured by the method described above. Step 2: Analyze the thickness of the heat seal layer. The thickness of the heat seal layer can be measured by cross-sectional observation using an electron microscope or X-ray CT measurement. A heat seal layer is applied to a non-oriented polypropylene film or a PET film so that the heat seal layer has the measured thickness, and the water vapor permeability of the heat seal layer alone can be inferred. Step 3: Calculate the water vapor permeability of the barrier layer alone based on the following formula from the water vapor permeability of the barrier laminate in step 1 and the water vapor permeability of the heat seal layer alone in step 2. At this time, the oxygen permeability of the paper substrate does not need to be taken into consideration if glassine paper is not used as the paper substrate (as a guideline, if the total light transmittance of the barrier laminate is less than 60%). 1 / P=1 / P1+1 / P2+···+1 / Pn P: Water vapor permeability of the barrier laminate, P1, P2, ... Pn: Water vapor permeability of each layer
[0090] (When materials for layers other than the barrier layer, such as the heat seal layer, are not available) For example, when the barrier laminate has a layer structure of paper substrate / barrier layer / heat seal layer, the calculation is as follows: The layer structure of the barrier laminate can be analyzed by cross-sectional observation using an electron microscope, X-ray CT measurement, or the like (analysis method). Step 1: Measuring the water vapor permeability of the barrier laminate The water vapor permeability of the barrier laminate can be measured by the method described above. Step 2: Analyze the material and thickness of the heat seal layer. The material of the heat seal layer can be analyzed by pyrolysis GC / MS, FT-IR analysis, Raman spectroscopy, etc. The thickness of the heat seal layer is measured by cross-sectional observation using an electron microscope or X-ray CT measurement, etc. The water vapor permeability of the heat seal layer alone can be estimated from the material and thickness of the heat seal layer. Step 3: Calculate the water vapor permeability of the barrier layer alone based on the following formula from the water vapor permeability of the barrier laminate in step 1 and the water vapor permeability of the heat seal layer alone in step 2. At this time, the oxygen permeability of the paper substrate does not need to be taken into consideration if glassine paper is not used as the paper substrate (as a guideline, if the total light transmittance of the barrier laminate is less than 60%). 1 / P=1 / P1+1 / P2+···+1 / Pn P: Water vapor permeability of the barrier laminate, P1, P2, ... Pn: Water vapor permeability of each layer
[0091] [Evaluation of redefibration (pulp recovery rate after redefibration)] A 30 g absolute dry mass of the barrier laminate was torn into 3-4 cm squares by hand and immersed in tap water at 20°C overnight. The barrier laminate was diluted with tap water to a concentration of 2.5% by mass, and then disintegrated for 20 minutes at 3000 rpm using a TAPPI standard disintegrator (Kumagaya Riki Co., Ltd.). The resulting pulp slurry was passed through a flat screen (Kumagaya Riki Co., Ltd.) equipped with a 6-cut (slit width 0.15 mm) screen plate, and refined in a water flow of 8.3 L / min. The undisintegrated material remaining on the screen plate was collected and dried in an oven at 105°C, and the bone dry mass was measured. The pulp recovery rate was calculated using the following formula. Pulp recovery rate (%)={bone dry mass (g) of barrier laminate used in test−bone dry mass (g) of undisintegrated material} / bone dry mass of barrier laminate used in test×100
[0092] [Heat seal peel strength measurement] Two barrier laminates were stacked with the coating layers facing each other, and heat-sealed at 150°C, 0.2 MPa, and 1 second using a heat seal tester (TP-701-B, manufactured by Tester Sangyo). The heat-sealed test pieces were left to stand for at least 4 hours in a room at a temperature of 23°C ± 1°C and a humidity of 50% ± 2%. The heat-sealed test pieces were then cut to a width of 15 mm and subjected to T-peel at a tensile speed of 300 mm / min using a tensile tester (Tensilon Universal Material Tester RTC-1250A, manufactured by A&D Co., Ltd.). The maximum load recorded was taken as the heat seal peel strength (N / 15 mm). EXAMPLES
[0093] Examples are given below to specifically explain the present invention, but the present invention is not limited to these examples. Unless otherwise specified, the following operations were performed under conditions of 25°C and a relative humidity of 50%RH. Furthermore, in the examples and comparative examples, "parts" and "%" respectively refer to "parts by mass" and "% by mass" unless otherwise specified.
[0094] Example 1 To 33.3 parts by mass of an aqueous dispersion of a layered inorganic compound (swellable mica (sodium tetrasilicic mica), average length 6.3 μm, aspect ratio approximately 1000, thickness approximately 5 nm, solids concentration 6 mass%, product name: NTO-05, manufactured by Topy Industries), 6.8 parts by mass of a self-emulsifying emulsion of ethylene-acrylic acid copolymer (solids concentration 29.2 mass%, product name: ZAIKXEN AC, manufactured by Sumitomo Seika Chemicals) was added with stirring, and 26.7 parts by mass of a self-emulsifying aqueous emulsion of hydroxy polyurethane (hydroxyl value: 235 mg KOH / g, solids concentration 30 mass%, product name: HPU-W013A, manufactured by Dainichi Seika Chemicals Mfg. Co., Ltd.) was further added and stirred. To this, 0.57 parts by mass of modified polyamide resin (surface charge 0.4 meq / g, solid content concentration 53 mass%, product name: SPI203(50)H, manufactured by Taoka Chemical Co., Ltd.) was added as a cationic resin and stirred. Furthermore, 0.30 parts by mass of 25 mass% ammonia aqueous solution was added and stirred. Further, dilution water was added to adjust the solid content concentration to 19 mass%, and a barrier layer coating liquid was prepared. The above barrier layer coating solution was applied to a paper substrate of 50 g / m 2 (One-sided gloss bleached kraft paper, manufactured by Oji F-Tex Co., Ltd.) 2 Apply the mixture so that it becomes evenly distributed, then dry it at 120℃ for 1 minute and then Further, as a heat seal layer coating liquid, a styrene acrylic aqueous dispersion (solid content concentration 48% by mass, product name: XP8829, manufactured by Seiko PMC Corporation) was diluted with water to a solid content concentration of 22% by mass, and a solid content of 5 g / m 2 The mixture was then dried at 120° C. for 1 minute to form a heat seal layer, thereby obtaining a heat sealable barrier laminate. Each layer was dried using a blower dryer. The heat seal layer has an oxygen permeability of 10.0 mL / m at 23°C and 50% RH. 2 10·day·atm and does not correspond to the barrier layer in the first embodiment.
[0095] Example 2 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the amount of the self-emulsifying emulsion of ethylene-acrylic acid copolymer in the barrier layer coating solution was 13.7 parts by mass, and the amount of the self-emulsifying aqueous emulsion of hydroxy polyurethane was 20.0 parts by mass, to obtain a heat-sealable barrier laminate.
[0096] Example 3 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the amount of swellable mica in the barrier layer coating solution was 50 parts by mass, to obtain a heat-sealable barrier laminate.
[0097] Example 4 Paper base material: bleached kraft paper 70g / m 2 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that OK Bashi Kraft (manufactured by Oji Materia) was used, to obtain a heat sealable barrier laminate.
[0098] Example 5 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer was changed to 5.1 parts by mass of a styrene-acrylic copolymer binder (solid content concentration 39 mass%, product name: JONCRYL HSL-9012, manufactured by BASF). A heat-sealable barrier laminate was obtained.
[0099] Example 6 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer was changed to 4.3 parts by mass of an acid-modified styrene-butadiene copolymer binder (solid content concentration 46% by mass, product name: LX407S12, manufactured by Zeon Corporation). A heat sealable barrier laminate was obtained.
[0100] Example 7 A self-emulsifying emulsion of ethylene-acrylic acid copolymer was mixed with 8.7 mass% of a polyolefin resin binder (solid content concentration 23 mass%, product name: HYDRECT HS, manufactured by DIC Corporation). A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except for changing the part, to obtain a heat-sealable barrier laminate.
[0101] Example 8 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the cationic resin in the barrier layer coating solution was changed to 1.90 parts by mass, to obtain a heat-sealable barrier laminate.
[0102] Example 9 A self-emulsifying emulsion of ethylene-acrylic acid copolymer was mixed with polyvinyl alcohol (product name: EXCEVAL HR-3010, manufactured by Kuraray Co., Ltd.) to a solids concentration of 10% by mass. A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the aqueous solution was changed to 20.0 parts by mass of the aqueous solution dissolved in water as described above, to obtain a heat sealable barrier laminate.
[0103] Example 10 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the heat seal layer coating liquid was changed to a polyolefin aqueous dispersion (solid content concentration 43 mass%, product name: Rhobarr320, manufactured by Dow), to obtain a heat sealable barrier laminate. The heat seal layer had a water vapor transmission rate of 50 g / m at 40°C and 90% RH. 2 ·days or more, and the oxygen permeability at 23°C and 50% RH is 10.0mL / m 2 10·day·atm and does not correspond to the barrier layer in the first embodiment.
[0104] Example 11 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the self-emulsifying emulsion of ethylene-acrylic acid copolymer was changed to 40.0 parts by mass of an aqueous solution of ammonium polyacrylate (solid content concentration 30% by mass, product name: Aron A-30, manufactured by Toa Gosei Co., Ltd.) adjusted to a solid content concentration of 5% by mass. To obtain a heat-sealable barrier laminate.
[0105] Example 12 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 10, except that the amount of the self-emulsifying emulsion of ethylene-acrylic acid copolymer added was changed to 3.4 parts by mass, and 10.0 parts by mass of an aqueous polyvinyl alcohol solution prepared by dissolving polyvinyl alcohol (product name: EXCEVAL HR-3010, manufactured by Kuraray Co., Ltd.) in water to a solids concentration of 10% by mass was added to the barrier layer coating solution.
[0106] Example 13 The barrier layer coating solution contained 31.7 parts by mass of a self-emulsifying emulsion of hydroxy polyurethane, 1.7 parts by mass of a self-emulsifying aqueous emulsion of ethylene-acrylic acid copolymer, and 1.90 parts by mass of a cationic resin. The coating amount of the heat seal layer was 3 g / m 2 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 10, except that the composition was changed to (based on solid content), to obtain a heat-sealable barrier laminate.
[0107] Example 14 A barrier layer was formed on a paper substrate in the same manner as in Example 1, except that the heat seal layer coating liquid was not applied, to obtain a barrier laminate.
[0108] Example 15 The barrier layer coating solution contained 83.3 parts by mass of swellable mica and 5.7 parts by mass of cationic resin, and the coating amount of the heat seal layer was 3 g / m 2A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 10, except that the composition was changed to (based on solid content), to obtain a heat-sealable barrier laminate.
[0109] Example 16 The amount of the self-emulsifying emulsion of ethylene-acrylic acid copolymer added was changed to 5.1 parts by mass, and 5.0 parts by mass of an aqueous polyvinyl alcohol solution prepared by dissolving polyvinyl alcohol (product name: EXCEVAL RS-1717, manufactured by Kuraray Co., Ltd.) in water to a solids concentration of 10% by mass was added to the barrier layer coating liquid, and the coating amount of the heat seal layer was changed to 3 g / m 2 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 10, except that the composition was changed to (based on solid content), to obtain a heat-sealable barrier laminate.
[0110] Comparative Example 1 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the amount of the self-emulsifying emulsion of ethylene-acrylic acid copolymer in the barrier layer coating solution was 34.2 parts by mass and the amount of the self-emulsifying aqueous emulsion of hydroxy polyurethane was 0 parts by mass, to obtain a heat-sealable barrier laminate.
[0111] Comparative Example 2 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the amount of swellable mica in the barrier layer coating solution was 0 parts by mass, and the amount of cationic resin was 0 parts by mass, to obtain a heat-sealable barrier laminate.
[0112] Comparative Example 3 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the cationic resin in the barrier layer coating solution was set to 0 parts by mass, to obtain a heat-sealable barrier laminate.
[0113] Comparative Example 4 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the cationic resin in the barrier layer coating solution was changed to 18.9 parts by mass, to obtain a heat-sealable barrier laminate.
[0114] Comparative Example 5 The procedure was the same as in Example 1, except that the swelling mica in the barrier layer coating solution was changed to 2 parts by mass of kaolin (engineered kaolin, average length 0.89 μm, aspect ratio about 33, thickness about 27 nm, solid content concentration 100% by mass, product name: Contour Extreme, manufactured by Imerys Co., Ltd.). Thus, a barrier layer and a heat seal layer were formed on the paper substrate, to obtain a heat sealable barrier laminate.
[0115] Comparative Example 6 A barrier layer and a heat seal layer were formed on a paper substrate in the same manner as in Example 1, except that the self-emulsifying aqueous emulsion of hydroxy polyurethane in the barrier layer coating liquid was changed to 80.0 parts by mass of an aqueous polyvinyl alcohol solution prepared by dissolving polyvinyl alcohol (product name: EXCEVAL AQ-4104, manufactured by Kuraray Co., Ltd.) in water to a solids concentration of 10% by mass, to obtain a heat-sealable barrier laminate.
[0116] [Sealing ability] The paper laminates of the examples and comparative examples were each formed into a pillow-shaped packaging bag and heat-sealed to produce a packaging bag. One side of the resulting packaging bag was cut, and a heat seal checker (product name: Ageless Seal Check, manufactured by Mitsubishi Gas Chemical Company, Inc., ingredients: high boiling point ester, high boiling point hydrocarbon, vegetable oil, azo-based oil-soluble dye) was dropped into the packaging bag to evaluate the presence or absence of liquid leakage from the sealed portion. A: The heat seal checker liquid is not leaking and is sealed. B: Heat seal checker liquid leaks, pinholes occur, no adhesion
[0117] Tables 1 to 3 show the formulation (ratio of mass parts of solid content), physical properties, evaluation results, oxygen permeability and water vapor permeability of the barrier layer itself, and the content (mass%) of each material in the barrier layer of each obtained barrier laminate. In the table, the unit of coating amount is g / m 2 and the unit of oxygen permeability is mL / m 2 ·day·atm, and the unit of water vapor permeability (measured at 40°C and 90% RH) is g / m 2 ·day The unit of heat seal strength is N / 15 mm. The redisintegrability is the recovery rate (mass%) of pulp after the barrier laminate is redisintegrated. In the table, the oxygen permeability of the barrier layer is the oxygen permeability of the barrier layer at 23° C. and 50% RH, and the water vapor permeability of the barrier layer is the water vapor permeability of the barrier layer at 40° C. and 90% RH. In the table, regarding the content in the barrier layer, "water-suspendable polymer, etc." indicates the total content of water-suspendable polymers other than hydroxypolyurethanes and water-soluble polymers other than hydroxypolyurethanes.
[0118] [Oxygen permeability of the barrier layer at 23℃ and 50% RH] The oxygen permeability of the barrier layer alone was measured using an oxygen permeability measuring device (MOCON, OX-TRAN2 / 22) at a temperature of 23°C and a relative humidity of 50%. 2 The barrier layer coating solution was applied to a paper substrate (manufactured by Oji F-Tex Co., Ltd.) in the formulation and coating amount of each Example and Comparative Example, and dried at 120°C for 1 minute to form a barrier layer. Furthermore, an isocyanate-based adhesive (manufactured by DIC Corporation, a mixture of 10 parts of DIC Dry LX-500 and 1 part of DIC Dry KW-75) was applied at 5 g / m 2 After coating, a CPP film (non-oriented polypropylene film: GP-32, manufactured by Hokuetsu Chemicals Co., Ltd.) having a thickness of 20 μm was laminated to form a laminated sheet. The oxygen permeability of the laminated sheet was measured at a temperature of 23°C and a relative humidity of 50% in accordance with JIS K7126-2:2006. The lower the oxygen permeability value, the better the oxygen barrier property. Note that the CPP film is laminated to make the measurement easier without being affected by the unevenness of the laminate, and the CPP film does not affect the oxygen permeability.
[0119] [Water vapor permeability of the barrier layer] The water vapor permeability was measured by applying the barrier layer coating liquid to a paper substrate (one-sided glossy bleached kraft paper, basis weight 50 g / m) with the formulation and coating amount of each Example and Comparative Example. 2 The coating was applied to a sheet of polyester (Oji F-Tex Co., Ltd.) and dried at 120°C for 1 minute to form a barrier layer. After that, measurements were made with the surface with the barrier layer facing inward in accordance with JIS-Z-0208:1976 (cup method) Method B (40°C±0.5°C, relative humidity 90%±2%).
[0120] [Table 1]
[0121] [Table 2] Example 14 did not adhere in the heat seal strength measurement.
[0122] [Table 3]
Claims
1. A barrier laminate having a barrier layer on at least one surface of a paper substrate, The barrier layer comprises a hydroxy polyurethane, a swellable layered silicate, and a cationic resin; the barrier layer further comprises at least one selected from the group consisting of a water-suspendable polymer other than the hydroxy polyurethane and a water-soluble polymer other than the hydroxy polyurethane; The content of the hydroxy polyurethane in the barrier layer is 40.0 to 80.0% by mass, the content of the swellable layered silicate in the barrier layer is 10.0 to 30.0% by mass, a barrier laminate, wherein the total content of the water-dispersible polymer other than the hydroxy polyurethane and the water-soluble polymer other than the hydroxy polyurethane in the barrier layer is 2.0 to 45.0 mass %.
2. 2. The barrier laminate according to claim 1, wherein the content of the cationic resin in the barrier layer is 1.0 to 20.0% by mass.
3. the water-dispersible polymer other than the hydroxy polyurethane includes at least one selected from the group consisting of a styrene-butadiene copolymer, an acrylic resin, an olefin-unsaturated carboxylic acid copolymer, and a polyolefin resin; 2. The barrier laminate according to claim 1, wherein the water-soluble polymer other than hydroxy polyurethane comprises at least one selected from the group consisting of a vinyl alcohol polymer, a (meth)acrylic acid polymer, polyethylene glycol, a water-soluble polyamide, a polyacrylamide, a polyamine, a polycarboxylic acid, and a water-soluble cellulose derivative.
4. the barrier laminate further has a heat seal layer on the side where the barrier layer is laminated, The heat seal layers of the barrier laminate were heat sealed together under conditions of 150° C., 0.2 MPa, and 1 second, and the heat seal strength was measured when the obtained sample was peeled off using a tensile tester.
2. The barrier laminate according to claim 1, having a strength of 2.0 N / 15 mm or more.
5. The total coating amount of the barrier layer and the heat seal layer is 12 g / m 2 The barrier laminate according to claim 4, wherein:
6. When a CPP film is laminated to the barrier laminate, the oxygen permeability at 23° C. and 85% RH is 10.0 mL / m 2 2. The barrier laminate according to claim 1, wherein the thermal expansion coefficient is 0.05-0.5×day·atm or less.
7. 2. The barrier laminate according to claim 1, wherein a recovery rate of pulp after redisintegration of the barrier laminate is 85 mass % or more.
8. A packaging bag comprising the barrier laminate according to any one of claims 1 to 7.
Citation Information
Patent Citations
Packaging paper
JP2021138434A
Gas barrier laminate and gas barrier seal sheet
JP2022158269A
JPP6958756B
Barrier laminate
WO2021106891A1
Gas barrier laminate
WO2021166910A1